Influence in the Blogosphere - Morzy, Mikołaj (Relacja wpływu w blogosferze, 2010)
In this paper we turn our attention to the fascinating problem of mining and ranking of blogs. We present a brief introduction to the problem of blog ranking and we summarize the related work on the subject. We focus on discovering the influence relation between blogs and blog posts in order to identify the most influential blogs using the context of a user's query. To do so, we transform blogs and blog posts into dual feature term-theme vectors representation. We use term vectors to align candidate blogs with the user query and we rank themes appearing in relevant vectors as possible answers. We also report the results of preliminary experiments conducted on our algorithm, which indicate that our algorithm is capable of delivering interesting and valuable answers.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 166-185
Keywords: blogs; data mining; influence; Web 2.0